Evaluación de modelos para la medición de riesgo de incumplimiento en créditos para las entidades financieras del cantón Babahoyo Provincia de Los Ríos - García Villafuerte, Zulema (2011)
This project analyzes the necessity of creating models that are validated with a practical application. They are developed under statistical methodologies, keeping in mind that the corporate management of the risk has become an important element for the administrative politics of the institutions dedicated to offer credits. It is presented the opportunity of generating a credit risk measurement method. This method will be undertaken since three models to reckon the probability of breach, with which comparisons of the kindnesses and disadvantages of each one of them can be performed. These models are...